Interaction effects of anxiety and outdoor activity spaces on frailty among nursing home residents in Jinan, China: Is there a gender difference? - Zhao, Meng; Qu, Tiange; Li, Yang; Wang, Yaqi; Li, Ming; Wang, Kefang (Frontiers in Public Health, 2023)
Background Anxiety and the physical environment are critical factors influencing frailty among older adults; however, the interaction effect of anxiety and the physical environment, such as outdoor activity spaces, on frailty has not been examined. This study aimed to investigate the interaction effect of anxiety and outdoor activity spaces on frailty and to identify differences by gender. Methods A total of 353 nursing home residents (197 women; 156 men; age ≥ 60 years) from 27 Chinese nursing homes were included in the analysis. Anxiety and frailty were analyzed using the Generalized Anxiety Disorder Scale and the FRAIL-NH Scale, respectively. Outdoor activity spaces were assessed through on-site observations using self-designed items. Demographic and socioeconomic information and health-related covariates were also collected. Interaction effect analyses were conducted using multilevel mixed-effects linear models. Results Anxiety and outdoor activity spaces had an interaction effect on frailty among nursing home residents (β = −1.32, 95% CI: −2.44, −0.20). However, further analysis demonstrated that this interaction effect was only significant in older women (β = −1.60, 95% CI: −2.93, −0.27) but not in older men (β = −0.23, 95% CI: −2.29, 1.82). Conclusions This study highlighted that gender differences should be considered when preventing frailty in older adults with anxiety. Furthermore, it may be beneficial for nursing homes to provide outdoor activity spaces and create a supportive living environment to help delay or reverse frailty among female nursing home residents.